Cryotherapy induces an increase in muscle stiffness - Point, M.; Guilhem, G.; Hug, F.; Nordez, A.; Frey, A.; Lacourpaille, L. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Although cold application (i.e., cryotherapy) may be useful to treat sports injuries and to prevent muscle damage, it is unclear whether it has adverse effects on muscle mechanical properties. This study aimed to determine the effect of air-pulsed cryotherapy on muscle stiffness estimated using ultrasound shear wave elastography. Myoelectrical activity, ankle passive torque, shear modulus (an index of stiffness) and muscle temperature of the gastrocnemius medialis were measured before, during an air-pulsed cryotherapy (-30°) treatment of 4 sets of 4 minutes with 1 min recovery in between, and during a 40-min post-cryotherapy period. Muscle temperature significantly decreased after the second set of treatment (10 min: 32.3 ± 2.5°C; P < 0.001), peaked at 29 min (27.9 ± 2.2°C; P < 0.001) and remained below baseline values at 60 minutes (29.5 ± 2.0°C; P < 0.001). Shear modulus increased by +11.5 ± 11.8% after the second set (10 min; P = 0.011), peaked at 30 min (+34.7 ± 42.6%; P < 0.001) and remained elevated until the end of the post-treatment period (+25.4 ± 17.1%; P < 0.001). These findings provide evidence that cryotherapy induces an increase in muscle stiffness. This acute change in muscle mechanical properties may lower the amount of stretch that the muscle tissue is able to sustain without subsequent injury. This should be considered when using cryotherapy in athletic practice